Biochar immobilized petroleum degrading consortium for enhanced granulation and treatment of synthetic oil refinery wastewater. (February 2022) - Wang, Qinghong; Deng, Jingmin; Liang, Jiahao; Jiang, Liangyan; Arslan, Muhammad; Gamal El-Din, Mohamed; Wang, Xin; Chen, Chunmao
Abstract: This study investigated the effect of biochar immobilized consortium for enhanced biotreatment of oil refinery wastewater in sequencing batch reactors. The control reactor (R0 ), and reactors with free bacterial consortium (R1 ), biochar (R2 ) and biochar immobilized consortium (R3 ) were operated in parallel. Results illustrated that granulation was faster in R2 and R3, the proportion of granules >0.45 mm was almost 30% higher than the R0 and R1 during the first 45 days. R3 exhibited optimum operational performance as highest removal efficiencies of COD (97.9%), oil (97.4%), NH4 + -N (97.2%) and TN (90.2%) at the end of the experiment. Biochar enriched microbial richness and diversity whereas inoculated consortium positively modulated the community structures. Higher abundance of inoculated Rhodococcus (4.81%) bacteria in R3 suggested successful formation of functional strains in the granular sludge. It concludes that the application of biochar immobilized consortium is a better choice for the treatment of refinery wastewater. Graphical abstract: Unlabelled Image Highlights: Bioaugmentation with free consortium and immobilized consortium were compared. Biochar immobilized consortium accelerated aerobic sludge granulation. Biochar immobilized consortium enhanced biotreatment of oil refinery wastewater. The presence of biochar improved microbial richness and diversity. Immobilization was beneficial in keeping functional inoculates in granules.